Price reactions to public announcements - B. Sailesh Ramamurtie; Michael J. Rebello (Federal Reserve Bank of Atlanta, 1996)
We employ a parametric rational expectations equilibrium model to study the impact of public information releases on private information acquisition and asset prices in a large economy. We demonstrate that investors treat public information as a substitute for privately acquired information. Their attempts to substitute public for private information can amplify or even reverse the effect of public information releases on price volatility. The direction of the resulting change in price volatility is dependent on the level of public information regarding asset payoffs, the variance of asset payoffs, and the extent of supply shocks, implying that firms may differ in their optimal information release policies.
Keywords: 330; Financial markets